THE EFFECT OF WARM COMPRESSES WITH RED GINGER ON REDUCING JOINT PAIN IN THE ELDERLY: CASE STUDY - Laras Supri Hartini; Asep Iskandar; Lita Heni Kusumawardani (International Journal of Biomedical Nursing Review, 2026)
Background: Elderly people who experience musculoskeletal disorders will cause pain in the joints. One of the treatments for joint pain is with non-pharmacological techniques. Purpose : This study intended to determine the effect of warm compresses with red ginger on reducing joint pain in the elderly. Results: There was a decrease in the scale of joint pain in the elderly after giving the intervention. Conclusion: There is a decrease in the scale of joint pain in the elderly after giving warm compress interventions with red ginger.